Two Implant Mandibular Overdentures: Clinical and Laboratory Procedures - Abdulgani, Azzaldeen; Abu-Hussein, Muhamad (Journal of Dentistry And Oral Implants, 2021)
Edentulism is considered a poor health outcome and may compromise quality of life. Implant-supported overdentures provide a good opportunity for dentists to improve the quality of life and oral health. Atrophic mandible poses a signiﬁcant challenge to successful oral rehabilitation with dental implants. The aim of this case report is to demonstrate the concept of immediate functional loading in the mandible using unsplinted implants to support a locator attachment supported overdenture.
Keywords: Implants; immediate loading; locator; mandibular overdenture